Analysis of The Effect of Drive Pulley Diameter Variation on Electric Motorcycle Performance - Eric Rico Ardiansyah; Indah Puspitasari; Nanang Romandoni; Prayogo Arie Bowo; Novi Indah Riani; Deni Nur Fauzi (Jurnal E-Komtek, 2025)
The primary objective of this study is to investigate how different sizes of drive pulleys influence the performance of an electric motorcycle equipped with a BLDC motor. This was approached using an experimental technique that combined dynotesting and road testing where three drive pulley diameters of 42T, 44T, and 46T were used. While the road tests were intended to measure the top speed of the motorcycle, the dynotests were aimed at acquiring the necessary data to calculate the torque and power. Based on the results of this study, an increase in the drive pulley's diameter will increase the speed of the electric motorcycle, although it will lower the torque. It was found that the 42T drive pulley offers the greatest torque, which is 16.54 Nm at a power of 5.2 HP, and the 46T drive pulley allows for the greatest speed of 63.37 km/h. It is thus apparent that for performance to be properly tailored to the motorcycle, a balance should be struck in line with the intended purpose, which can either be acceleration or the cruising speed.